Pembuatan Deterjen Krem Mampu Urai Hayati (Biodegradable Detergen) - Budi Utami; Hendartini Hendartini (Jurnal Kimia dan Kemasan, 1995)
Experiment of household cream detergent has been done in a laboratory scale by preparing several formulations containing several different types of substances. Each formulation has been tested according to the SNI 06 - 0162 - 1987. The formulation which the SNI requirement is formulation VIII which has stable paste, Ph = 10,8 , surfactant content = 24,03 %, and water insoluble matter = 2,63 % .